Award-Winning Economists Speak on Contemporary Economic Issues : Subtitle Here - Kimmel, Jean (Book collections on Project MUSE., 2016)
Five award-winning economists tackle a diverse range of topics and show how applied economics has evolved to give policymakers a more nuanced approach to policy development.